TECHNOLOGICAL ARCHITECTURES FOR AI INTEGRATION IN PEDAGOGICAL PRAXIS: EVALUATING ADAPTIVE LEARNING ECOSYSTEMS (Multidisciplinary Journal of Science and Technology, 2026)
Educational delivery paradigms require structural overhauls driven by algorithmic mediation to optimize knowledge transfer. This investigation quantifies the pedagogical efficacy of implementing recurrent neural network (RNN) architectures and natural language processing (NLP) algorithms within undergraduate environments. Utilizing a prospective, controlled quasi-experimental design, 450 students were stratified into a traditional digital cohort and an experimental AI-mediated cohort. Analysis revealed a profound divergence in conceptual application. Students engaged within the AI-driven ecosystem demonstrated a statistically significant enhancement in post-intervention cognitive assessment scores, elevating from a baseline mean of 45.2 ± 3.1 to 78.4 ± 4.2, fundamentally outperforming the control group (61.3 ± 5.1, p < 0.001). Predictive pathfinding algorithms simultaneously reduced cognitive overload instances by 41.6%. Embedding specific neural network topologies into institutional learning environments represents an immediate strategic necessity to personalize the zone of proximal development at an industrial scale.